Laser-Induced Modification of Ag and Cu Metal Nanoparticles Formed by Exploding Wire Technique in Liquid - R. Humud, Hammad; J. Kadhem, Saba (Iraqi Journal of Science, 2023)
This research aims to find a method to synthesize nanoparticles of important metals in the fields of medicine and electronics, with high purity small in size and narrow size distribution. And it characterized by simplicity, efficiency and high productivity. To achieve this aim the effects of laser irradiation on silver and copper colloids prepared by exploding wire technique in double distilled and deionized water (DDDW) have been studied. The laser irradiation was performed using laser radiation fluence about 4 J/cm2 at 532 nm wavelength. Additional irradiation of colloids resulted in the changes of particles morphology, which were monitored by absorption spectroscopy and transmission electron microscopy methods. It was found that both the mean size of the nanoparticles and their size distribution controlled by changing the number of laser pulses. It was found that the decrease in particle size depends on the laser wavelength, SPR absorption peak position for the metals nanoparticles before laser irradiation and the exposure time. The combination of the two techniques exploding wire and laser ablation in liquids is possible to synthesize nanoparticles with small sizes less than 5 nm, small size distribution and characterized by simplicity, efficiency and high productivity. Nanoparticles prepared by this method have high purity, where there are no chemicals in the particle synthesis process.